PENGARUH PENERAPAN MODEL PEMBELAJARAN RECIPROCAL TEACHING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA - Hariyati Hariyati; Nurmala R (Mathematics Education And Application Journal (META), 2019)
AbstractThis research is a quasi-experimental research (quasi experimental), which aims to see whether or not there is an influence of the application of the Reciprocal Teaching learning model to the ability to understand mathematical concepts of Grade VIII students of SMPN 4 Tarakan. Descriptive analysis results with an average achievement of the ability to understand mathematical concepts of students in the experimental class is 79.7414 and 60.2778 in the control class. The highest value obtained by students in the experimental class was 97.50 and the lowest value was 52.50 while in the control class the highest value was 82.50 and the lowest value was 45.00. For the average achievement of all indicators of students' understanding of mathematical concepts for the experimental class is higher than in the control class. So, the application of Reciprocal Teaching learning model can be said to affect the ability of understanding the mathematical concepts of eighth grade students of SMPN 4 Tarakan. Keywords: Experiments, Reciprocal Teaching Learning Model, Ability to Understand Student Mathematical ConceptsAbstrakPenelitian ini merupakan penelitian eksperimen semu (quasi esperimental), yang bertujuan untuk melihat ada atau tidaknya pengaruh penerapan model pembelajaran Reciprocal Teaching terhadap kemampuan pemahaman konsep matematika siswa kelas VIII SMPN 4 Tarakan. Hasil analisis deskriptif dengan rata-rata pencapaian kemampuan pemahaman konsep matematika siswa di kelas eksperimena dalah 79,7414 dan pada kelas kontrol 60,2778. Adapun nilai tertinggi yang diperoleh siswa di kelas eksperimen sebesar 97,50 dan nilai terendah sebesar 52,50 sedangkan pada kelas kontrol nilai tertinggi sebesar 82,50 dan nilai terendah sebesar 45,00. Untuk rata-rata pencapaian dari seluruh indikator kemampuan pemahaman konsep matematika siswa untuk kelas eksperimen lebih tinggi dibandingkan pada kelas kontrol. Jadi, penerapan model pembelajaran Reciprocal Teaching dapat dikatakan berpengaruh terhadap kemampuan pemahaman konsep matematika siswa kelas VIII SMPN 4 Tarakan.Kata Kunci: Ekperimen, Model Pembelajaran Reciprocal Teaching, Kemampuan Pemahaman Konsep Matematika Siswa